Identifikasi Kandungan Saponin dalam Ekstrak Kamboja Merah (Plumeria rubra L.) dan Daya Surfaktan dalam Sediaan Kosmetik - Nurzaman, Fulka; Djajadisastra, Joshita; Elya, Berna (Jurnal Kefarmasian Indonesia, 2018)
Saponin is a group of compounds contained in natural materials that have amphiphilic properties and can reduce surface tension. The reduction of surface tension caused by a soap compound (Latin = sapo) that can disrupt hydrogen bonds in water. Red frangipani plant (Plumeria rubra) is known to have saponin content. The research objectives were to identify the saponin content of red frangipani plant extract (Plumeria rubra) which could reduce the surface tension. Part of red frangipani plant (flowers, leaves and stems) was extracted using five kinds of solvents. Each of the extracts obtained was then tested for saponin content qualitatively. Extract from each part of the plant (flower, leaf, and stem) which has the highest foam was selected then tested surface tension using surface tensionmat equipment. The result of qualitative saponin test showed that flower, stem and flower extract of red frangipani with aqua demineralisata solvent had the highest saponin content compared to extract with other solvent. The content of saponins in plumeria rubra extract either from the leaves, stems or flowers could decrease the surface tension with the best results obtained from the flower extract with 8,61% of Critical Micelle Concentration (CMC).